599 The effect of Low-Level LASER therapy on osseointegration. Can LASER therapy improve bone/implant contact? A preliminary study on rats (Balneo and PRM Research Journal, 2024)
Abstract: Bone fractures can lead to disability and a prolonged rehabilitation period. In some patients, the risk of complications can increase if the healing process is not efficacious or if the metallic implants are loose. Photobiomodulation is a physiotherapeutic method of treatment that can stimulate the cell proliferation and reduce the simpthomatology. We evaluated the effect of LASER therapy on the osseointegration of smooth titanium implants in 12 female rats that suffered fractures on both tibiae. The LASER therapy was performed second day after surgery on half of the rats on both tibia for 7 sessions, every 48 hours. Both tibia were removed in the control and experimental group at 2,4 and 6 weeks after finalizing the last photobiomodulation session. The methods of assesment were micro-CT scans, histology and mechanical tests. The mechanical tests show better bone/implant stability in favor of the experimental group at all 3 times of tissue prelevation. Histological fidings show more bone lamellas in the experimental group after 2 weeks, but no significant differences afterward. The micro-CT imaging show no significant differences between the 2 groups. LASER therapy could prove as an important tool in orthopedic patients and can potentially reduce the rehabilitation time.